Participação do sistema endocanabinoide do hipotálamo dorsomedial emeventos aversivos - Thércia Guedes Viana (2016)
The dorsomedial hypothalamus (DMH) is an important integrative nucleus for behavioral, endocrine and autonomic responses. The stimulation of DMH by excitatory amino acids, such as glutamate, promotes defensive responses related to anxiety. On the other hand, the endocannabinoid system seems to inhibit these reactions. This work tested the hypothesis that the endocannabinoid system inhibit the aversive reactions in this structure. To test this hypothesis, aversive responses were induced by intra-DMH NMDA injection, an agonist of NMDA glutamatergic receptors. Animals were submitted to stereotaxic surgery for implantation of a cannula into DMH. After 7 days, theywere placed in an observation box and recorded for 5 min. The injection of NMDA intra-DMH elicited escape reactions, consisting of crossings and jumps. This effect was prevented by a CB1 agonist (ACEA) and a CB2 agonist (JWH133). The endocannabinoid 2-AG-hydrolysis inhibitor (URB602), but not anandamide-hydrolysis inhibitor (URB597) prevented defensive behavior. URB602 reverted cardiovascular response augmentation. None of the treatments changed corticosterone levels. The behavioral effects of URB602 were prevented by both CB1 (AM251) and CB2 (AM630) receptors antagonists. The pretreatment with AM251 followed by a dose of NMDA that does not produce effect by itself failed to elicit aversive reactions. NMDA administration increased c-Fos expression in the Dorsomedial Hypothalamus (DMH), ventromedial hypothalamus (VMH), and dorsomedial (dmPAG) and dorsolateral(dlPAG) columns do the periaqueductal gray. The expression of the enzyme that synthesizes 2-AG (DAGL) was increased on DMH and VMH. The colocalization of c-Fos/DAGL positive cells increased on DMH, VMH anddlPAG. It is concluded that the endocannabinoid 2-AG modulates defensive responses induced by activation of the DMH, probably through CB1 and CB2 cannabinoid receptors.